2018
DOI: 10.1002/polb.24775
|View full text |Cite
|
Sign up to set email alerts
|

High‐Strain Shape Memory Behavior of PLA–PEG Multiblock Copolymers and Its Microstructural Origin

Abstract: Shape memory properties of two thermoplastic multiblock copolymers composed of poly(lactic acid) (PLA) and poly(ethylene glycol) (PEG) having different PEG‐segment lengths of 6 and 11 kDa were studied. The performance as a shape memory polymer at high strain level (600%) and its interrelations with shape‐programming conditions, molecular orientation, and microstructural changes are elucidated. A significant contribution of strain‐induced crystallization of PLA segments to the improvement of temporary shape fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…For instance, glycolic acid is the most studied co-monomer used with lactic acid [ 34 , 74 , 75 ]. Block co-polymerization of PLA with poly(ethylene glycol) (PEG) is another common technique used to enhance the biodegradability of polylactide [ 34 , 75 , 76 , 77 ]. A study revealed a solvent-free synthesis of a PLA–PEG block copolymer with enhanced biodegradability [ 78 ].…”
Section: Bio-based Materials For Packaging Applicationsmentioning
confidence: 99%
“…For instance, glycolic acid is the most studied co-monomer used with lactic acid [ 34 , 74 , 75 ]. Block co-polymerization of PLA with poly(ethylene glycol) (PEG) is another common technique used to enhance the biodegradability of polylactide [ 34 , 75 , 76 , 77 ]. A study revealed a solvent-free synthesis of a PLA–PEG block copolymer with enhanced biodegradability [ 78 ].…”
Section: Bio-based Materials For Packaging Applicationsmentioning
confidence: 99%
“…Strategies to chemically improve its shape memory (SM) performance include copolymerization , and urethane formation that involved complicated chemical processes. Conversely, physical blending with a flexible biopolymer, as the reversible switching phase, has proven to be an unpretentious and effective strategy to modulate its SM performance while preserving its biodegradability .…”
Section: Introductionmentioning
confidence: 99%
“…For the phase separation morphology, a fixed phase was used to maintain the deformed shape, whereas the reversible phase plays an important role in storing and releasing internal stress. Interestingly, the synthesized ABA (where A = hard block and B = soft block) triblock copolymers , that combine the phase separation with good compatibility between two phases are one of the ideal candidates for shape-memory polymers. However, a complicated synthetic process is inevitable for intrinsically thermoresponsive SMPs, which may hinder their development.…”
Section: Introductionmentioning
confidence: 99%